Concomitant Glomus Tumor with CRPS in the Hand - Jeong, Hyeong Jun (The Korean Pain Society, 2013)
Glomus tumors are benign tumors that account for 1% to 5% of all soft tissue tumors of the hand and are characterized by a triad of sensitivity to cold, localized tenderness and severe paroxysmal pain. Paroxysmal pain is a symptom common not only in glomus tumors but also in CRPS, and the hand is one of the commonly affected sites in patients with both glomus tumors and CRPS. Therefore, it is not easy to clinically diagnose glomus tumors superimposed on already affected region of CRPS patients. We report a case of glomus tumor concomitantly originating with CRPS at the hand.